ANALISA PEMILIHAN MATERIAL BANGUNAN DALAM MEWUJUDKAN GREEN BUILDING (STUDI KASUS: GEDUNG KANTOR PERWAKILAN BANK INDONESIA SOLO) - Dianita, Ratna; Adi S, Taufik Lilo; Sutrisno, Sutrisno (Pendidikan Teknik Bangunan, 2014)
Abstract: The purposes of this study were to know (1). The types of building materials that used on KPwBI Solo building in terms of architecture aspect. (2). Whether the building materials thatused on KPwBI Solo building, related to the environmental safety standards materials or not. (3). The advantages and disadvantages of building materials that used on KPwBI Solo building. (4).What were the impact of the use of building materials on KPwBI Solo building. The results of An Analysis were (1). Evaluated in terms of architecture aspect, the types of building materialsthat used in the KPwBI Solo building, include: a). As floor coverings, used: Ceramics, Ceramic Heavy Duty, Homogeneous Tile, Marble, Granite, Parquette, and Andhesit. b). For walls, used: Homogeneous Tile, Glass, Marble, Granite, Temple Stone and Wood Panels. c). For ceiling,used: Gypsum Board, Acoustic Tile and Water Resistant Gypsum. (2). Building materials of KPwBI Solo, the standards of environment safety materials. (3). The advantages and disadvantages of each material were one aspect to be considered in the selection of building materials in the KPwBI Solo building. (4). The used of building materials in the KPwBI Solo building, give positive impact related to energy saving, resource saving, water saving, environmental health and building users, as well as the comfort of the building users.Keywords: green building, environmental friendly material, material election, material impact